Parental involvement and student creativity: a three-level meta-analysis - Fan, Huiyong; Feng, Yuxiang; Zhang, Yichi (Frontiers in Psychology, 2024)
Introduction The Ecological Systems Model of Creativity Development (ESMCD) proposes that parental involvement positively impacts student creativity. However, prior empirical studies present mixed results, including positive, negative, and no correlations between these variables. Methods To synthesize these inconsistent primary studies, the current study conducted a systematic meta-analysis synthesizing 30 primary studies involving 37 independent samples with 70 effect sizes and a total N = 20,906 participants. Results The results demonstrated: (1) an overall significant small, positive correlation (r = 0.101) between parental involvement and student creativity; (2) significant small, positive correlations between specific involvement types (autonomy support r = 0.144; behavioral control r = 0.133; content support r = 0.131) and creativity, alongside a significant small, negative correlation between psychological control and creativity (r = −0.117); (3) no statistically significant moderating effects of student grade level, parental gender, region, or publication type. Discussion This systematic meta-analytic review consolidates empirical evidence indicating that parental involvement positively predicts students’ creativity, while highlighting the detrimental impact of psychological control on creative outcomes. Further research elucidating the mechanisms underlying these relations is critical for informing parenting approaches and education policies seeking to foster creativity development among students.